Online/Offline Ciphertext Retrieval on Resource Constrained Devices. (21st July 2016) - Jiang, Peng; Mu, Yi; Guo, Fuchun; Wang, Xiaofen; Wen, Qiaoyan
Abstract : The ciphertext retrieval is of paramount importance for data confidentiality and utilization in mobile cloud environment. The receiver, usually equipped with resource constrained devices, retrieves data stored in the cloud server by submitting a confidential request (or trapdoor) to the cloud. Previous schemes need at least one exponentiation operation in group G for each keyword to generate the trapdoor, which is quite burdensome for mobile devices to support such computational cost. The computational cost of trapdoor generation limits the application of ciphertext retrieval, especially in a wireless environment. In this paper, we propose the first online/offline ciphertext retrieval (OOCR) scheme, where the trapdoor generation is split into two phases: offline phase and online phase . Most of the computation of the trapdoor could be performed in the offline phase prior to knowing the keyword. The generation of the real trapdoor with keyword can be done efficiently in the online phase. The most challenging task is to resist the so-called insider attacks, which is about keyword guessing attacks from the untrusted cloud server. We also build a novel framework to resist insider attacks and propose an OOCR scheme against insider attacks. Our semantic security proof and performance analysis demonstrate that the proposal is practical for mobile cloud applications.